The synthesis of 4-arylcoumarines via cu-catalyzed arylation 4-hydroxycoumarine with the substituted phenylboronic acids - F. Rafiee; O. Nazari (Results in Chemistry)
In this research, the catalytic activity of Fe3O4@SiO2-NNO-CuII nanocomposite was investigated in Suzuki coupling reaction of 4- tosylcoumarine with various substituted arylboronic acids. This reusable copper nanocatalyst activated CO bond and with the exit of tosylate group, CC bond was formed between 4-position of coumarin and arylboronic acid derivative. The substituted 4-arylcoumarines were obtained in high yields and short reaction times under mild reaction. The prepared nanocatalyst was easily separated from the reaction mixture using an external magnet and could reused in the next reaction runs for at least 4 cycles.